2004
DOI: 10.1271/bbb.68.1888
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Glutamine Synthetase ofPseudomonas taetrolensY-30: An Enzyme Usable for Production of Theanine by Coupling with the Alcoholic Fermentation System of Baker’s Yeast

Abstract: Concentrated cell-extract of Pseudomonas taetrolens Y-30, isolated as a methylamine-assimilating organism, formed gamma-glutamylethylamide (theanine) from glutamic acid and ethylamine in a mixture containing the alcoholic fermentation system of baker's yeast for ATP-regeneration. Glutamine synthetase (GS), probably responsible for theanine formation, was isolated from the extract of the organism grown on a medium containing 1% methylamine, 1% glycerol, 0.5% yeast extract, and 0.2% polypepton as carbon and nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
47
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…1C). 12) The results suggested that theanine production in high concentrations can be achieved by increasing the GS concentration in the reaction mixture. 13) This was unsuccessful, however, due to the low reactivity of P. taetrolens Y-30 GS to ethylamine, resulting in difficulty in dissolving large amounts of the enzyme.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…1C). 12) The results suggested that theanine production in high concentrations can be achieved by increasing the GS concentration in the reaction mixture. 13) This was unsuccessful, however, due to the low reactivity of P. taetrolens Y-30 GS to ethylamine, resulting in difficulty in dissolving large amounts of the enzyme.…”
mentioning
confidence: 98%
“…10,11) In order to overcome these shortcomings, we have investigated theanine production from glutamic acid and ethylamine using the theanine synthetase-like enzyme, in which sugar fermentation of dried baker's yeast cells was coupled as an ATP-regenerating system (coupled fermentation with energy transfer). [12][13][14][15] In earlier reports, [12][13][14] we indicated the principle of coupled fermentation with energy transfer using the glutamine synthetase (GS; L-glutamate:ammonia ligase, ADP-forming, E.C. 6.3.1.2, Fig.…”
mentioning
confidence: 98%
“…Although several methods for preparing theanine have been reported, [13][14][15][16][17] they are usually complicated and show unsatisfactory yield. As described in previous papers, 18,19) theanine production by -glutamyl transfer reaction of bacterial glutaminase 20) or -glutamyl transpeptidase 21) has certain shortcomings with respect to supply of substrate (glutamine) and side reactions that lower product yield on glutamine.…”
mentioning
confidence: 99%
“…18,19,22) In this method, a catalytic amount of another substrate ATP is regenerated by sugar fermentation of baker's yeast.…”
mentioning
confidence: 99%
See 1 more Smart Citation